Development and validation of a reversed-phase high performance liquid chromatography method for the simultaneous estimation of rosuvastatin calcium and telmisartan in fixed-dose complex dual-layer tablets in six dosage forms - Choi, Min Nyeong; Park, Y. J.; Kim, Joo Eun (Indian Journal of Pharmaceutical Sciences, 2021)
Fixed dose complex dual-layer tablets of telmisartan and rosuvastatin calcium have been used for the treatment of hypertension and hyperlipidemia. However, the current United States Pharmacopoeia analysis method is limited by the need for twice the time and cost owing to analysis for each active pharmaceutical ingredient present separately. Due to the critical limitations in establishing simultaneous analysis methods for both active pharmaceutical ingredients, there is an urgent need for an analysis method that can be applied for immediate use by researchers. The objective of this study was to develop and validate a simultaneous quantitative assay using a rapid and selective high performance liquid chromatography method for the analysis of rosuvastatin calcium and telmisartan in fixed dose combination dual-layer tablet dosage forms. This method used Kinetex C18 (5 µm, 4.6×150 mm) columns at a flow rate of 1.0 ml/ min and Ultraviolet-visible detector set at a wavelength of 242 nm. The separation was carried out using an ammonium phosphate monobasic buffer (pH 3.0) and methanol at a ratio of 300:700 as the mobile phase. The retention times of rosuvastatin calcium and telmisartan were 2.2 and 4.3 min respectively. The system suitability was 0.41 % for rosuvastatin calcium and 0.63 % for telmisartan, and the peak of each component showed complete separation from disturbance peaks. The correlation coefficient of the active pharmaceutical ingredients was approximately 0.999 when the concentration of rosuvastatin calcium was in the range of 4.44-26.6 µg/ml and the concentration of telmisartan was 0.176-106.6 µg/ml, this indicates good linearity. The recovery rate relative to the amount added was 97.0–99.6 % for rosuvastatin calcium and 95.5-102.2 % for telmisartan. Precision and solution stability were within the permissible range. Validation acceptance criteria were met in all cases. This simultaneous quantitative analysis method was successfully applied to the quality assessment of six fixed dose combination dual-layer tablets containing various amounts of rosuvastatin calcium and telmisartan.
Keywords: Dissolution; High performance liquid chromatography; Method validation; Rosuvastatin calcium; Simultaneous estimation; Telmisartan